The Influence of Cooperative Learning Strategies on Elementary School Students' Mathematics Learning Outcomes: A Literature Review - Nevia Nevia (Ludi Litterarri, 2025)
Mathematics learning in elementary schools requires an approach capable of increasing student engagement and addressing the tendency for low learning outcomes. One recommended alternative is a cooperative learning strategy oriented towards group collaboration and social interaction. This study aims to examine the influence of cooperative learning strategies on elementary school students' mathematics learning outcomes through a literature review. The research method used a qualitative approach with a literature review of relevant articles, journals, and research published in the last five years. The analysis process was carried out through the identification, categorization, and synthesis of empirical findings regarding the effectiveness of cooperative learning models. The results of the study indicate that cooperative learning strategies, through models such as STAD, Jigsaw, and Think-Pair-Share, are consistently able to improve students' conceptual understanding, learning motivation, and mathematics learning outcomes. In addition, these strategies also have a positive impact on students' social skills, communication, and self-confidence. However, their effectiveness depends on thorough instructional planning, the role of the teacher as a facilitator, and the support of contextual factors such as class size and authentic assessment. Thus, cooperative learning is worthy of being an innovative alternative to improve the quality of mathematics learning in elementary schools